The Stafford Gallery the greatest art collection of Regency London - Humfrey, Peter 1947- (Unicorn Press, 2019)
The book will provides the first detailed history of the Bridgewater collection. The story extends from the 3rd Duke of Bridgewater's purchases in Rome in the 1750s, then on to the major acquisitions of the 1790s (especially from the Orleans collection), then through the incorporation of the collection into the Stafford Gallery by the 2nd Marquess of Stafford (1st Duke of Sutherland), and finally to its reinstallation by Lord Francis Egerton in the new Bridgewater House in 1851.0As well as providing a detailed account of the personalities and differing motives of three generations of collectors and owners, the book examines the ways in which the collection was arranged and displayed. It also discusses reactions to it by contemporaries, from sophisticated critics such as William Hazlitt, to the general public, and analyses major publications on it such as the four-volume illustrated catalogue by William Young Ottley of 1818. The illustrations will include many works sold from the collection after 1946 and now widely dispersed.
Keywords: Sutherland, George Granville Leveson-Gower of -- 1758-1833; Bridgewater, Francis Egerton -- Duke of -- 1736-1803; Geschichte; Kunst; Sammlung; Präsentation